THE PREFERENCES OF SELECTING THE EFFECTIVE AND EFFICIENT LEARNING MEDIA IN STUDENTS : Fulfilling Student Information Needs in Completing Academic Tasks in the Sociology of Education Perspective - BAKHTIYAR; YANUASTRID SHINTAWATI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
Research aims to describe the preferences for selecting learning media to meet the information needs of students in completing academic assignments. The research object is based on the accuracy of analysis based on detailed comprehensive studies of the main focus of content, the selection of learning media to complete student academic tasks, quickly and effectively, which have now adapted to the era of the industrial revolution 4.0, towards digitalization in information seeking. The research has the scope of in-depth analysis based on and focused on main studies, namely the preference for selecting learning media to meet the information needs of students in completing academic tasks. Analyzing research, requires realistic critical thinking, the application of a conceptual occurs in the historical period, in the past or when it is happening, so that a historical approach is appropriate, the main characteristic of which is to dominate realistic critical investigation of the development of a thought or term. Primary information sources are used as primary data. Historical approach data collection, empowering research libraries through reading various literatures based on subjected reading materials, preferences, selection of learning media, student information needs and completion of academic tasks. The analysis is carried out by qualitative descriptive analysis, based on sources of analysis originating from a variety of theoretical, research and non-research reading materials. Research predominates the description and evaluation of factual facts in order to obtain problem-solving solutions that are embodied in social phenomena, the selection of learning media for the completion of student academic tasks. Validity is realized through in-depth analysis through content analysis, which is useful for analyzing the meaning of the most important concepts in research. Observation of student activities in fulfilling information needs is used as a support for theory construction. The result of the research is that most students in Indonesia prefer to use digital media rather than print media to fulfill their information needs in completing their academic assignments.